RETRACTED: Actual problems of the influence of IT technologies on personality development - Priymak Elena; Makhova Anna (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001